Antibacterial Activity of Kecombrang (Etlingera elatior) Stems Against Skin Infection-Causing Bacteria - Adini, Syilvi; Kumala, Shirly; Setyahadi, Siswa (Sciences of Pharmacy, 2025)
Skin infections caused by Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes often exhibit resistance to conventional treatments. This issue has led to the exploration of medical plants, such as kecombrang stems (Etlingera elatior), which are known for their antibacterial properties. This study aimed to evaluate the antibacterial activity of kecombrang stem and to identify its active compounds. The methanolic extract of kecombrang stems was tested against the three bacteria using the disc diffusion method at concentrations of 80%, 40%, and 20%. The Minimum Inhibitory Concentration (MIC) was determined using the microdilution method and an ELISA reader. TLC-Bioautography was employed to identify the antibacterial compounds present in the extract. The methanol extract of kecombrang stems exhibited antibacterial activity against S. aureus, S. epidermidis, and P. acnes, with an inhibition zone diameter ranging from 9.23 ± 0.472 to 25.53 ± 0.378 mm. The MIC results showed that the minimum concentration of 78.12 ppm could inhibit the growth of S. aureus by 33.74%, S. epidermidis by 14.45%, and P. acnes by 3.5%. The results of TLC Bioautography analysis indicate that flavonoids exhibit antibacterial properties. The kecombrang stem has the potential to serve as an antibacterial agent against bacteria that cause skin infections.